2018
DOI: 10.1111/jzo.12636
|View full text |Cite
|
Sign up to set email alerts
|

Comparative trophic ecology of two sympatric canids in the Brazilian Pampa

Abstract: Studies on resource utilization by carnivores are essential to assess the role of the species in the ecosystem. These studies help us to understand the mechanisms that influence vertebrate community structure and the relationships between predators and prey. The aims of this study were to compare and describe the food habits of the sympatric Pampas fox (Lycalopex gymnocercus) and crab‐eating fox (Cerdocyon thous) in the Brazilian Pampa, and to evaluate the food niche overlap between them, and infer aspects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 41 publications
(62 reference statements)
3
15
0
3
Order By: Relevance
“…Thus, these canids can be considered phylogenetically similar species among other carnivores in the same area. Furthermore, these foxes are the most common canids in southern Brazil, have similar morphology and overlap their ecological niche in many aspects (Bossi et al., 2019; Kasper et al., 2016). Therefore, the occurrence of similar bone deformities in both species in the same area suggests they might be affected by a common environmental cause.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, these canids can be considered phylogenetically similar species among other carnivores in the same area. Furthermore, these foxes are the most common canids in southern Brazil, have similar morphology and overlap their ecological niche in many aspects (Bossi et al., 2019; Kasper et al., 2016). Therefore, the occurrence of similar bone deformities in both species in the same area suggests they might be affected by a common environmental cause.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these canids can be considered phylogenetically similar species among other carnivores in the same area. Furthermore, these foxes are the most common canids in southern Brazil, have similar morphology and overlap their ecological niche in many aspects (Bossi et al, 2019;Kasper et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the RAI values and the naïve occupancy (i.e., the proportion of sampling site where a species is recorded) showed that the Pampas fox is the most common carnivore species in the coastal area of the southern part of Buenos Aires province, followed by the Geoffroy's cat. The numeric dominance of Pampas fox is not surprising, because this canid is a very adaptable carnivores, capable of opportunistically feed on a variety of prey (e.g., Bossi, Migliorini, Santos, & Kasper, 2019;Castillo, Birochio, Lucherini, & Casanave, 2011;Farias & Kittlein, 2008) and still relatively common in the agroecosystems of the Pampas. Conversely, the relatively high frequency of records and occupancy of the Geoffroy's cat in our study area, especially when compared to those of C. chinga and G. cuja, was unexpected, based on the available information on the present-day Pampas landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Because Pampas foxes readily eats carrion and have been reported to prey on several animals associated to saline water, such as crabs, crustaceans, and even fish (García and Kittlein, 2005;Lucherini and Luengos Vidal, 2008;Bossi et al, 2019), these canids could be expected to use the areas close to the shoreline more intensively than other carnivores. We found little support for this hypothesis.…”
Section: Discussionmentioning
confidence: 99%